Considering Gowok Cultural Traditions as Prostitution is a Logical Fallacy - Achmad Fadilah (Jurnal Dinamika Hukum, 2022)
Gowok is a cultural tradition that ever existed in Banyumas. This tradition aims to provide understanding, education, and training for a boy who is about to become a teenager or is about to enter the stage of marriage, by a woman who will act as his partner, so that when the boy gets married he can provide physical and spiritual support for his wife. The lack of information about the Gowok cultural tradition makes the construction of the social reality of the community towards the tradition to be bad and negative. Some even think that the Gowok cultural tradition is hidden prostitution. This assumption needs to be straightened out again because it is not entirely true. There are several significant differences between the Gowok cultural tradition and prostitution. This study uses historical research methods with qualitative analysis which is based on literary literacy research and Sin Po newspaper documents in 1941. This study shows that the Gowok cultural tradition experiences misperceptions that continue to mean decadence and ultimately lead to a logical fallacy.Keyword: Gowok, Ronggeng Dukuh Paruk, local wisdom, prostitution, logical fallacy